Kesalahan Pengucapan Vokal Bahasa Inggris Mahasiswa 'Kelas Berbicara' UIN Sunan Gunung Djati - Munandar, Ilham; Indira, Dian; Darmayanti, Nani (Adabiyyāt: Jurnal Bahasa dan Sastra, 2021)
Error pronunciation is one of the language learning processes. It may happen to all of the language learners, especially in learning a foreign language which the goal is to have more than one language in language skill. This research aims to describe the types of error pronunciation of English vowels which is spoken by ‘Speaking Class’ students in the Language Center of UIN Sunan Gunung Djati. The method used in this research is the descriptive qualitative method. This research uses the combination of vowel theories from Roach, McMahon, and Kelly, as well as the error analysis theory from Brown and Crystal. Based on the result, there are three types of error pronunciation of English, namely vowel addition of [e], [ɪ], [a], [ɜː], [ə]; vowel substitution of [ə], [æ], [uː], [ɔː], [ɪ], [iː], [e], [ʌ], [ɑː], [ɒ], [ɜː], [aɪ], [aʊ], [ɪə], [eɪ], [əʊ], [ɔɪ], [eə], [aʊə]; and vowel omission of [ɪ], [ə], [a], [e].